Characterization of Pectobacterium carotovorum subsp. carotovorum isolates from a recent outbreak on cabbage in Bosnia and Herzegovina - Popović, Tatjana; Jelušić, Aleksandra; Marković, Sanja; Iličić, Renata (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2020)
The causal agent of soft rot disease associated with a cabbage outbreak in Semberijaregion, Bosnia and Herzegovina, in 2018 was identified and characterized. Symptoms appearedin the form of water-soaked lesions on leaves and specific odour. Disease incidence rangedfrom 20% to 30%. The causal pathogen was isolated on nutrient agar (NA), King’s B andcrystal violet pectate (CVP) media. Eight creamy-white, round and convex bacterial isolates,which produced characteristic pits on CVP medium were taken as representative. They weregram negative, facultative anaerobe, oxidase negative, catalase positive, nonfluorescenton King’s B medium, levan and arginine dehydrolase negative. The isolates were able tocause soft rot on cabbage and potato tuber slices 24 h after inoculation under conditionsof high relative humidity. Polymerase chain reaction (PCR) was performed for preliminaryidentification by using three specific primer sets: F0145/E2477 (specific for Pectobacteriumcarotovorum subsp. carotovorum), Br1f/L1r (specific for P. carotovorum subsp. brasiliensis) andECA1f/ECA2r (specific for P. atrosepticum). All isolates produced the band size of 666 bp withF0145/E2477 primer pair, indicating that they belong to the species P. carotovorum subsp.carotovorum. Further genetic characterization was based on sequence analysis of the gapAand mdh housekeeping genes. BLAST analysis confirmed 99.39% (Q. cover 100%, E. value0.0) and 100% (Q. cover 100%, E. value 0.0) identity of the isolates with P. carotovorum subsp.carotovorum strains deposited in the NCBI database as M34 (KY047594) for gapA and Pcc t0437(KC337296) for mdh genes, respectively. Phylogenetic analysis showed genetic homogeneityamong the cabbage isolates.
Keywords: Pectobacterium; cabbage; identification; characterization